Handbook of Pragmatics 24th Annual Installment. - Östman, Jan-Ola (Handbook of Pragmatics ;, 2022)
The IPrA Handbook of Pragmatics provides easy access to the different topics, traditions and methods which together make up the field of Pragmatics, broadly conceived as the cognitive, social and cultural study of language and communication, i.e. the science of language use. Also available as Online Resource:https://benjamins.com/online/hop.